Nicolae Al. POP – Founder of the Bucharest School of Relational Marketing - Carmen Acatrinei (Amfiteatru Economic, 2025)
Professor Nicolae Al. Pop, PhD, Doctor Honoris Causa was born in 1948 in Oradea, the beautiful city on the banks of the Crișul Repede River, today recognized as one of Europe's foremost strongholds of Art Nouveau / Jugendstil / Secession architecture. In 1965, Professor Pop graduated from the “Emanuil Gojdu” National College in Oradea, the most prestigious educational institution in the county, with a tradition dating back to 1919. Among its alumni are 16 members of the Romanian Academy, including corresponding members and members of other scientific academies. Subsequently, Professor Pop pursued his studies at the Bucharest University of Economic Studies (ASE), within the Faculty of Commerce, graduating in 1970.